A STRONG LATERAL SHEAR VELOCITY GRADIENT AND ANISOTROPY HETEROGENEITY IN THE LOWERMOST MANTLE BENEATH THE SOUTHERN PACIFIC - Ford S.R.; Garnero E.J.; McNamara A.K. (My University, 2006)
Velocity heterogeneity and seismic anisotropy in the D" region beneath the southern Pacific Ocean is investigated using broadband shear waves from southwest Pacific and South American earthquakes recorded by permanent and temporary stations in Antarctica, Australia, South America, and on islands in the South Pacific. Shear velocity perturbations (δVs) are inferred from the differential travel times between hand-picked horizontally polarized (SH) direct or diffracted S arrivals and vertically polarized (SV) SKS arrivals. Derived patterns in δVs roughly agree with global shear velocity models but reveal a stronger shear velocity lateral gradient north of approximately 52°S where δVs transitions from approximately +0.5 to - 1.0% (relative to radially averaged reference models) over less than 600 km along the base of D". Waveform analyses provide an even stronger constraint on the transitional region, where there is a change in waveform behavior occurring over length scales less than 300 km. Differential travel times between SKKS and SKS, calculated by cross-correlating SKS with Hilbert transformed SKKS, support large δVs amplitudes and help to constrain the location of the transitional region. Anisotropy in D" (ks) is inferred from handpicked differential travel times between the SV and SH components of direct or diffracted S and display a slight spatial trend where the SH component precedes the SV in the north and east of the study area but arrives after SV in the center and southwest of it. However, there is high ks variability in the center of the study region. There is no apparent correlation between δVs and ks. Abrupt changes in the character of velocity and anisotropy in this region of D" may be related to chemical heterogeneity at the boundary of the Pacific Superswell, as well as small-scale convection in the deep mantle. Copyrigth 2006 by the American Geophysical Union.